Spettatore in naufragio. Vecchie lanterne magiche e nuove immersività virtuali (Mantichora. Italian Journal of Performance Studies, 2020)
The total immersion (sensorial and physical) of the 3D cinematographic experience was already a great worry even for early cinema. During pre-cinema era, every new invention aimed to turn those shadows of light more and more “real”. Even the magic lantern shows, widespread throughout the XVII, aimed to recreate life, to excite and to amuse the public, through its simples still images but producing physical sensations adding the movement. So, before becoming narrative, cinema aesthetic was much closer to performing arts. Also, the relation with its public was more physical and spectators were more involved and active in the shows: as during the Hale’s Tours, a kind of physical “journeys” on a moving train passing through paint landscapes. The dioramas as well were all devices that attempted to dip physically the spectators into the world representation. When cinema stopped showing and started telling stories, the physical involvement of the spectator turned to a psychical one. 3D experience tries in a way to return to a total and physical immersion of the spectator into the fiction; which is quite closer to virtual reality than to the classic experience of cinema, as we knew it up until now. This paper focus on the upcoming “future” of cinema promised by the 3D new technology, and the nature of the cinematographic scene, which is still maybe that elsewhere that while leaving the spectators off, outside the scene, it immerse them in its deepest inside.